Low-dielectric high-heat-resistance copper-clad plate and preparation method thereof
By using cage polysilsesquioxane resin and other materials in copper clad plates to form low-dielectric high-heat-resistant copper clad plates, the problems of high dielectric constant and large dielectric loss in high-frequency signal transmission in traditional copper clad plates are solved, and the problem of high dielectric constant and high dielectric loss in high-frequency signal transmission is achieved. Lower signal delay and energy loss, improving the heat resistance and signal transmission efficiency of the equipment.
Patent Information
- Application Number
- CN202411729547.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional copper clad plates have too high dielectric constant and large dielectric loss in high-frequency and high-speed signal transmission, resulting in signal delay and energy loss, affecting signal integrity and equipment reliability, and lacking heat resistance and mechanical strength, making it difficult to meet 5G and the rest. High frequency technology demand.
It uses low-dielectric high-heat-resistant copper clad plate composed of cage polysilsesquioxane resin, DCPD modified epoxy resin, isocyanate modified epoxy resin, styrene anhydride copolymer, flame retardant and inorganic filler. By forming a highly ordered micropore structure and crosslinking network, the dielectric constant and dielectric loss are reduced, and the glass transition temperature and mechanical properties are improved.
It significantly reduces the dielectric constant and dielectric loss, improves the heat resistance and mechanical properties of the material, extends the service life of the equipment, reduces signal delay and energy loss, and enhances signal transmission efficiency and equipment reliability.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper clad laminates and relates to a low-dielectric and high-heat-resistant copper clad laminate and a preparation method thereof. Background Art
[0002] Copper clad laminate is the main material for manufacturing printed circuit boards (PCBs), and therefore is also an indispensable basic electronic material for any electronic product. With the advancement of science and technology and the development of society, the application scope of electronic products is becoming more and more extensive, from smart phones to self-driving cars, from smart homes to industrial automation, which has led to a continuous increase in the demand for copper clad laminates. Especially in the field of communication technology, the popularization of the fifth generation of mobile communication technology (5G) has not only promoted a leap in data transmission speed, but also promoted the rapid development of emerging fields such as the Internet of Things, telemedicine, and virtual reality. However, this series of technological advances has put forward higher requirements for electronic materials. High-frequency and high-speed signal transmission has become an important development trend of current and future electronic and communication products, which requires copper clad laminates to have lower dielectric constants and dielectric losses to reduce signal attenuation and improve transmission efficiency.
[0003] Traditional copper clad laminate materials often expose many deficiencies when facing high-frequency and high-speed signal transmission. For example, a high dielectric constant will increase signal delay, while high dielectric loss will lead to increased energy loss, both of which will directly affect the integrity and quality of the signal. In addition, due to the characteristics of high-frequency signals, traditional copper clad laminates may also face the problem of increased electromagnetic interference, further affecting the reliability and stability of electronic equipment. In extreme cases, these problems may cause increased leakage current and severe heating of integrated circuits, thereby shortening the service life of the equipment and even causing safety risks. Therefore, in order to meet the technical needs of the 5G era and even in the distant future, the research and development of copper clad laminates is moving towards reducing dielectric constants, reducing dielectric losses, improving heat resistance, and enhancing mechanical strength. At the same time, environmental protection has also become one of the important considerations in the research and development of copper clad laminate materials. How to achieve green production while ensuring high performance has become a topic of common concern within and outside the industry. Summary of the invention
[0004] The purpose of the present invention is to address the above problems existing in the prior art and to provide a low-dielectric and high-heat-resistant copper-clad laminate with excellent dielectric properties and heat resistance.
[0005] The purpose of the present invention can be achieved by the following technical solutions: A low-dielectric and high-heat-resistant copper-clad laminate comprises a prepreg and copper foil, wherein the prepreg is composed of glass cloth and glue, and the glue comprises the following raw materials in parts by mass: 5-20 parts of cage-type polysilsesquioxane resin, 30-50 parts of DCPD-modified epoxy resin, 20-40 parts of isocyanate-modified epoxy resin, 20-50 parts of styrene anhydride copolymer, 10-40 parts of bisphenol A epoxy resin, 20-40 parts of flame retardant, 40-70 parts of inorganic filler, 0.5-5 parts of accelerator, 2-7 parts of auxiliary agent, and 50-100 parts of organic solvent.
[0006] The present invention utilizes cage-type polysilsesquioxane resin (POSS) to form a highly ordered microporous structure in the material, thereby significantly improving the porosity of the material. This structure not only helps to reduce the dielectric constant and dielectric loss tangent of the material, but also improves its dielectric properties. The POSS molecule contains 8 epoxy groups, which increase the collision probability during the reaction process, making the generated network structure have a higher cross-linking density, thereby improving the glass transition temperature (Tg) and mechanical properties of the material, so that it can still maintain good physical and chemical properties in a high temperature environment.
[0007] Dicyclopentadiene phenol (DCPD) modified epoxy resin is a high-performance epoxy resin with extremely high adhesion, extremely low hygroscopicity, low dielectric constant and dielectric loss tangent, and high heat resistance. The cured DCPD modified epoxy resin exhibits excellent heat resistance and chemical stability, enabling it to maintain good performance in high temperature and corrosive environments. This resin is particularly suitable for electronic devices and composite materials that require high reliability and long life.
[0008] Isocyanate-modified epoxy resin, through its unique chemical structure, gives the material excellent heat resistance and toughness, as well as high peel strength and a good processing window. This modified resin can form a dense cross-linked network during the curing process, which improves the overall performance of the material, especially under high temperature and dynamic load. Its high peel strength also makes the material more reliable and durable in practical applications.
[0009] Styrene-maleic anhydride copolymer (SMA) is a polymer material obtained by free radical polymerization of styrene and maleic anhydride. Its structure contains two units with different characteristics, styrene and maleic anhydride. Maleic anhydride can continue to react and introduce other functional groups to achieve further modification. SMA has excellent high temperature resistance, hardness and dimensional stability, as well as high impact strength. These properties make it have broad application prospects in the fields of electronic packaging, coatings and composite materials.
[0010] In the above-mentioned low dielectric and high heat-resistant copper clad laminate, the cage-type polysilsesquioxane includes at least one of octavinyl cage-type polysilsesquioxane, octaepoxy cage-type polysilsesquioxane, octaphenyl cage-type polysilsesquioxane, and tetravinyltetraepoxy cage-type polysilsesquioxane.
[0011] In the above-mentioned low-dielectric and high-heat-resistant copper-clad laminate, the flame retardant is at least one of decabromodiphenylethane, tetrabromobisphenol A, tricresyl phosphate, tributyloxyethyl phosphate, triphenyl phosphate, zinc borate, and antimony trioxide.
[0012] In the above-mentioned low-dielectric and high-heat-resistant copper-clad laminate, the inorganic filler is at least one of silicon micropowder, magnesium hydroxide, aluminum hydroxide, talcum powder, silicon carbide nanoparticles, mica powder, and calcium silicate.
[0013] In the above-mentioned low-dielectric and high-heat-resistant copper-clad laminate, the accelerator is at least one of 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-ethyl-4-phenylimidazole or boric acid.
[0014] In the above-mentioned low-dielectric and high-heat-resistant copper-clad laminate, the auxiliary agent is at least one of an epoxy silane coupling agent, an amino silane coupling agent, a vinyl silane coupling agent and an acrylate silane coupling agent.
[0015] In the above-mentioned low-dielectric and high-heat-resistant copper-clad laminate, the organic solvent is at least one of DMF, acetone, butanone, cyclohexanone, propylene glycol methyl ether, toluene, xylene, and ethylene glycol methyl ether.
[0016] The present invention also provides a method for preparing the above-mentioned low-dielectric and high-heat-resistant copper-clad laminate, the method comprising the following steps: S1, prepare the above raw materials; S2, stirring polyhedral oligomeric silsesquioxane (POSS) resin, DCPD modified epoxy resin, isocyanate modified epoxy resin, styrene anhydride copolymer, bisphenol A type epoxy resin and an organic solvent; S3, then add flame retardant, inorganic filler and auxiliary agent to homogenize and emulsify, and then add accelerator to stir to obtain glue solution; S4, applying the glue solution on the electronic grade glass fiber cloth, and then baking it to obtain a prepreg; S5. Coating copper foil on the surface of the prepreg and hot pressing to obtain a copper clad laminate.
[0017] In the above-mentioned method for preparing a low-dielectric and high-heat-resistant copper-clad laminate, the homogenization and emulsification in step S3 is carried out in a homogenizer, and the homogenization and emulsification time is 2-4 hours.
[0018] In the above-mentioned method for preparing a low-dielectric and high-heat-resistant copper-clad laminate, the baking treatment temperature in step S4 is 100-200° C. and the time is 8-15 minutes.
[0019] In the above-mentioned method for preparing a low-dielectric and high-heat-resistant copper-clad laminate, the pressure during hot pressing is 300-400PSI, the temperature is 180-230°C, and the time is 60-120min.
[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention effectively reduces the dielectric constant of the copper clad laminate by introducing cage-type polysilsesquioxane resin (POSS), which is crucial for reducing signal delay and improving signal transmission efficiency. The introduction of POSS resin not only improves the dielectric properties of the material, but also increases the glass transition temperature (Tg) of the material, which means that the material can maintain its physical and chemical properties unchanged at higher temperatures and is suitable for a wider range of environmental conditions.
[0021] 2. The copper clad laminate of the present invention adopts a variety of modified epoxy resins and inorganic fillers. These components work together to not only enhance the heat resistance of the material, but also greatly improve the modulus and tensile strength of the material and reduce the water absorption rate. This means that the copper clad laminate can still maintain good physical properties in a high temperature environment, reduce dimensional changes caused by temperature changes, and improve the dimensional stability of the material.
[0022] 3. The present invention uses a specific ratio of resin and inorganic filler to make the copper clad laminate exhibit excellent copper foil peeling strength, ensuring that the bonding force between the copper foil and the substrate will not be easily weakened under long-term use or harsh conditions. At the same time, the material also has excellent CAF (conductive anode wire) resistance, which can effectively prevent internal short circuits caused by moisture and extend the service life of electronic products.
[0023] 4. The copper clad laminate preparation method of the present invention is simple, which greatly improves the yield rate in the production process and reduces the manufacturing cost. The prepared copper clad laminate also has good UV Blocking (ultraviolet blocking) and AOI (automatic optical inspection) compatibility. DETAILED DESCRIPTION
[0024] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.
[0025] The raw materials used in the embodiments of the present invention are as follows: The DCPD-modified epoxy resin is HP-7200H from DIC of Japan; The isocyanate-modified epoxy resin is Tongyu TER296K75; The cage-type polysilsesquioxane resin is an octaepoxy cage-type silsesquioxane, preferably G-POSS from HybridPlastics; The styrene anhydride copolymer is EF40 produced by Polyscope of the Netherlands; The flame retardant was decabromodiphenylethane, purchased from SAYTEX 8010 produced by Albemarle Corporation, USA; The inorganic filler is surface-treated nano-scale silicon powder, D50 is 0.2 μm, purchased from Jiangsu Lianrui NQS205; The accelerator is 2-phenylimidazole produced by SHIKOKU Co., Ltd. of Japan; The auxiliary agent was 3-glycidyloxypropyltriethoxysilane, purchased from Shin-Etsu KBE-403; The organic solvent is preferably a 1:1 mixed solvent of DMF and butanone. Embodiment 1:
[0026] S1. Prepare the following raw materials by mass: 10 parts of cage-type polysilsesquioxane resin, 40 parts of DCPD-modified epoxy resin, 25 parts of isocyanate-modified epoxy resin, 30 parts of styrene anhydride copolymer, 30 parts of bisphenol A epoxy resin, 25 parts of flame retardant, 60 parts of inorganic filler, 0.7 parts of accelerator, 2.5 parts of auxiliary agent, and 80 parts of organic solvent; S2, stirring polyhedral oligomeric silsesquioxane (POSS) resin, DCPD-modified epoxy resin, isocyanate-modified epoxy resin, styrene anhydride copolymer, bisphenol A epoxy resin and organic solvent for 2.5 h until the resin is completely dissolved in the solvent; S3, then add flame retardant, inorganic filler and auxiliary agent in a homogenizer for homogenization and emulsification for 3 hours, then add accelerator and stir for 2 hours to obtain glue solution; S4, impregnating the electronic grade glass fiber cloth with glue by a vertical glue applicator, and then baking at 180° C. for 10 min to obtain a prepreg; S5. Copper foil is coated on the upper and lower surfaces of the prepreg and hot-pressed to obtain a copper-clad laminate, wherein the pressure during hot-pressing is 350 PSI, the temperature is 197° C., and the time is 90 min. Embodiment 2:
[0027] S1. Prepare the following raw materials by mass: 5 parts of cage-type polysilsesquioxane resin, 30 parts of DCPD-modified epoxy resin, 20 parts of isocyanate-modified epoxy resin, 20 parts of styrene anhydride copolymer, 10 parts of bisphenol A epoxy resin, 20 parts of flame retardant, 40 parts of inorganic filler, 0.5 parts of accelerator, 2 parts of auxiliary agent, and 50 parts of organic solvent; S2, stirring polyhedral oligomeric silsesquioxane (POSS) resin, DCPD-modified epoxy resin, isocyanate-modified epoxy resin, styrene anhydride copolymer, bisphenol A epoxy resin and organic solvent for 2.5 h until the resin is completely dissolved in the solvent; S3, then add flame retardant, inorganic filler and auxiliary agent in a homogenizer for homogenization and emulsification for 3 hours, then add accelerator and stir for 2 hours to obtain glue solution; S4, impregnating the electronic grade glass fiber cloth with glue by a vertical glue applicator, and then baking at 180° C. for 10 min to obtain a prepreg; S5. Copper foil is coated on the upper and lower surfaces of the prepreg and hot-pressed to obtain a copper-clad laminate, wherein the pressure during hot-pressing is 350 PSI, the temperature is 197° C., and the time is 90 min. Embodiment 3:
[0028] S1. Prepare the following raw materials by mass: 20 parts of cage-type polysilsesquioxane resin, 50 parts of DCPD-modified epoxy resin, 40 parts of isocyanate-modified epoxy resin, 50 parts of styrene anhydride copolymer, 40 parts of bisphenol A epoxy resin, 40 parts of flame retardant, 70 parts of inorganic filler, 5 parts of accelerator, 7 parts of auxiliary agent, and 100 parts of organic solvent; S2, stirring polyhedral oligomeric silsesquioxane (POSS) resin, DCPD-modified epoxy resin, isocyanate-modified epoxy resin, styrene anhydride copolymer, bisphenol A epoxy resin and organic solvent for 2.5 h until the resin is completely dissolved in the solvent; S3, then add flame retardant, inorganic filler and auxiliary agent in a homogenizer for homogenization and emulsification for 3 hours, then add accelerator and stir for 2 hours to obtain glue solution; S4, impregnating the electronic grade glass fiber cloth with glue by a vertical glue applicator, and then baking at 180° C. for 10 min to obtain a prepreg; S5. Copper foil is coated on the upper and lower surfaces of the prepreg and hot-pressed to obtain a copper-clad laminate, wherein the pressure during hot-pressing is 350 PSI, the temperature is 197° C., and the time is 90 min. Embodiment 4:
[0029] The only difference from Example 1 is that all the raw materials are stirred once to obtain glue solution, the glue solution is impregnated on electronic grade glass fiber cloth by a vertical glue applicator, and then baked at 180° C. for 10 minutes to obtain a semi-cured sheet.
[0030] Comparative Example 1: The only difference from Example 1 is that the amount of cage-type polysilsesquioxane resin added to the raw material is 1 part.
[0031] Comparative Example 2: The only difference from Example 1 is that the amount of cage-type polysilsesquioxane resin added to the raw material is 30 parts.
[0032] Comparative Example 3: The only difference from Example 1 is that no cage-type polysilsesquioxane resin is added to the raw materials.
[0033] Comparative Example 4: The only difference from Example 1 is that the amount of DCPD-modified epoxy resin added to the raw material is 20 parts.
[0034] Comparative Example 5: The only difference from Example 1 is that the amount of DCPD-modified epoxy resin added to the raw material is 60 parts.
[0035] Comparative Example 6: The only difference from Example 1 is that no DCPD-modified epoxy resin is added to the raw materials.
[0036] Comparative Example 7: The only difference from Example 1 is that the amount of isocyanate-modified epoxy resin added to the raw materials is 10 parts.
[0037] Comparative Example 8: The only difference from Example 1 is that the amount of isocyanate-modified epoxy resin added to the raw materials is 50 parts.
[0038] Comparative Example 9: The only difference from Example 1 is that no isocyanate-modified epoxy resin is added to the raw materials.
[0039] Table 1: Test results of dielectric and heat resistance properties of copper clad laminates prepared in Examples 1-4 and Comparative Examples 1-9
[0040] Table 2: Physical property test results of copper clad laminates prepared in Examples 1-4 and Comparative Examples 1-9
[0041] In summary, the copper clad laminate of the present invention adopts a variety of modified epoxy resins and inorganic fillers. These components work together to not only enhance the heat resistance of the material, but also greatly improve the modulus and tensile strength of the material and reduce the water absorption rate. This means that the copper clad laminate can still maintain good physical properties in a high temperature environment, reduce dimensional changes caused by temperature changes, and improve the dimensional stability of the material.
[0042] The parts of the embodiments herein that are not exhaustive of the midpoint values of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the listed or unlisted embodiments of the scheme of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.
[0043] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical schemes composed of any combination of the above technical features. The above is a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.
[0044] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A low dielectric and high heat resistant copper clad laminate, characterized in that: The copper clad laminate comprises a prepreg and copper foil, wherein the prepreg is composed of glass cloth and glue, and the glue comprises the following raw materials in parts by weight: 5-20 parts of cage-type polysilsesquioxane resin, 30-50 parts of DCPD-modified epoxy resin, 20-40 parts of isocyanate-modified epoxy resin, 20-50 parts of styrene anhydride copolymer, 10-40 parts of bisphenol A epoxy resin, 20-40 parts of flame retardant, 40-70 parts of inorganic filler, 0.5-5 parts of accelerator, 2-7 parts of auxiliary agent, and 50-100 parts of organic solvent.
2. A low dielectric and high heat resistant copper clad laminate according to claim 1, characterized in that: The cage type polysilsesquioxane includes at least one of octavinyl cage type polysilsesquioxane, octaepoxy cage type polysilsesquioxane, octaphenyl cage type polysilsesquioxane, and tetravinyltetraepoxy cage type polysilsesquioxane.
3. A low dielectric and high heat-resistant copper clad laminate according to claim 1, characterized in that: The flame retardant is at least one of decabromodiphenylethane, tetrabromobisphenol A, tricresyl phosphate, tributyloxyethyl phosphate, triphenyl phosphate, zinc borate and antimony trioxide.
4. The low dielectric and high heat-resistant copper clad laminate according to claim 1, characterized in that: The inorganic filler is at least one of silicon micropowder, magnesium hydroxide, aluminum hydroxide, talcum powder, silicon carbide nanoparticles, mica powder and calcium silicate.
5. The low dielectric and high heat-resistant copper clad laminate according to claim 1, characterized in that: The accelerator is at least one of 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-ethyl-4-phenylimidazole and boric acid.
6. The low dielectric and high heat-resistant copper clad laminate according to claim 1, characterized in that: The auxiliary agent is at least one of an epoxy silane coupling agent, an amino silane coupling agent, a vinyl silane coupling agent and an acrylate silane coupling agent.
7. The low dielectric and high heat-resistant copper clad laminate according to claim 1, characterized in that: The organic solvent is at least one of DMF, acetone, butanone, cyclohexanone, propylene glycol methyl ether, toluene, xylene, and ethylene glycol methyl ether.
8. A method for preparing a low dielectric and high heat-resistant copper-clad laminate as claimed in claim 1, characterized in that: The method comprises the following steps: S1. Prepare the raw materials according to claim 1; S2, stirring a cage-type polysilsesquioxane resin, a DCPD-modified epoxy resin, an isocyanate-modified epoxy resin, a styrene anhydride copolymer, a bisphenol A-type epoxy resin, and an organic solvent; S3, then add flame retardant, inorganic filler and auxiliary agent to homogenize and emulsify, and then add accelerator to stir to obtain glue solution; S4, applying the glue solution on the electronic grade glass fiber cloth, and then baking it to obtain a prepreg; S5. Coating copper foil on the surface of the prepreg and hot pressing to obtain a copper clad laminate.
9. The method for preparing a low dielectric and high heat-resistant copper-clad laminate according to claim 8, characterized in that: Step S3: homogenization and emulsification is carried out in a homogenizer, and the homogenization and emulsification time is 2-4 hours.
10. The method for preparing a low dielectric and high heat-resistant copper clad laminate according to claim 8, characterized in that: The baking treatment temperature in step S4 is 100-200° C. and the time is 8-15 minutes.
Citation Information
Patent Citations
Low dielectric constant polyhedral oligomeric silsesquioxane (POSS) / epoxy resin hybrid material and preparation method
CN103146141A
Halogen-free high-frequency and high-speed copper-clad plate and preparation method thereof
CN105415778A
Toughened heat-resistant modified epoxy resin and preparation method thereof
CN106751516A
Halogen-free epoxy resin composition, prepreg containing same, laminated board and printed circuit board
CN106832764A
Low-dielectric and low-dielectric-loss halogen-free resin composition, prepreg and laminated board
CN110066493A
Cited By
High-temperature-resistant low-dielectric epoxy resin prepreg as well as preparation method and application thereof
CN120349549A
High-temperature-resistant low-dielectric epoxy resin prepreg, preparation method and application thereof
CN120349549B
Resin glue solution for copper-clad plate, high-heat-resistance copper-clad plate and preparation method
CN120484446A
Resin glue solution for copper-clad plate, high-heat-resistant copper-clad plate and preparation method thereof
CN120484446B
INS high-temperature-resistant and scratch-resistant automobile decorative film and preparation method thereof
CN120623920A